Deer mouse hemoglobin exhibits a lowered oxygen affinity owing to mobility of the E helix. Corrigendum. Issue 6 (31st May 2013) - Inoguchi, Noriko; Oshlo, Jake R.; Natarajan, Chandrasekhar; Weber, Roy E.; Fago, Angela; Storz, Jay F.; Moriyama, Hideaki
<x xml:space="preserve">Abstract</x> The affiliation of two authors in the article by Inoguchi et al. [(2013). Acta Cryst. F69, 393–398] is corrected.